2022
DOI: 10.1093/nar/gkab1274
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin binds to G-quadruplex repeats found at telomeres and gene promoters

Abstract: G-quadruplex (G4) structures that can form at guanine-rich genomic sites, including telomeres and gene promoters, are actively involved in genome maintenance, replication, and transcription, through finely tuned interactions with protein networks. In the present study, we identified the intermediate filament protein Vimentin as a binder with nanomolar affinity for those G-rich sequences that give rise to at least two adjacent G4 units, named G4 repeats. This interaction is supported by the N-terminal domains o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…In a previous study ( Ceschi et al, 2022 ) the Q-PARSE bioinformatics tool was used to search sequences containing two contiguous G4-forming elements in the region covering 100 nucleotides upstream the transcription starting site of human genes. The search was extended to both, the forward and reverse strands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study ( Ceschi et al, 2022 ) the Q-PARSE bioinformatics tool was used to search sequences containing two contiguous G4-forming elements in the region covering 100 nucleotides upstream the transcription starting site of human genes. The search was extended to both, the forward and reverse strands.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been observed that Vimentin, an intermediate filament (IF) protein, is able to interact selectively with G4-repeats. This complex involves only the tetrameric form of the protein that is found within the nucleus as a soluble nuclear fraction ( Ceschi et al, 2022 ). Although an architectural role has long been considered the main function of Vimentin, it is well recognized that it also participates to various signaling cascades and it can act as a transcriptional regulator within metastatic cancer cells ( Mergui et al, 2010 ), ( Jang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the proteins that are able to selectively recognize G4 repeats could be a strategy to address the specific functions of these DNA structures. Pull-down experiments on nuclear extracts were performed to identify proteins that preferentially bind G4 repeats rather than isolated G4s ( Figure 6 ) [ 68 ]. Remarkably, it turns out that vimentin, an intermediate filament protein, can bind G4 repeats with high affinity.…”
Section: G4 Repeats and Protein Recruitment In Cellmentioning
confidence: 99%
“… Outline of a pull-down approach leading to the discovery of vimentin as a G4 repeat selective binder (adapted from [ 68 ]). …”
Section: Figurementioning
confidence: 99%